Equipping Durum Wheat—Thinopyrum ponticum Recombinant Lines With a Thinopyrum elongatum Major QTL for Resistance to Fusarium Diseases Through a Cytogenetic Strategy - Kuzmanović, Ljiljana; Mandalà, Giulia; Tundo, Silvio; Ciorba, Roberto; Frangella, Matteo; Ruggeri, Roberto; Rossini, Francesco; Gevi, Federica; Rinalducci, Sara; Ceoloni, Carla (Frontiers in Plant Science, 2019)
Prompted by recent changes in climate trends, cropping areas and management practices, Fusarium head blight (FHB), a threatening disease of cereals worldwide, is also spreading in unusual environments, where bread wheat (BW) and durum wheat (DW) are largely cultivated. The scarcity of efficient resistance sources within adapted germplasm is particularly alarming for DW, mainly utilized for human consumption, which is therefore at high risk of kernel contamination by health-dangerous mycotoxins (e.g. deoxynivalenol = DON). To cope with this scenario, we looked outside the wheat primary genepool and recently transferred an exceptionally effective FHB resistance QTL (Fhb-7EL) from Thinopyrum elongatum 7EL chromosome arm onto a Th. ponticum 7el1L arm segment, containing additional valuable genes (including Lr19 for leaf rust resistance and Yp for yellow pigment content), distally inserted onto 7DL of BW lines. Two such lines were crossed with previously developed DW-Th. ponticum recombinants, having 7el1L distal portions on 7AL arms. GISH analysis showed homologous pairing, enabled by 7el1L segments common to the BW and DW recombinant chromosomes, to occur with 42-78% frequency, depending on the shared 7el1L amount. Aided by 7EL/7el1L-linked markers, 7EL+7el1L tetraploid recombinant types were isolated in BC1 progeny to DW of all cross combinations. Homozygous 7EL+7el1L recombinant plants and null segregates selected in BC2F2 progenies were challenged by Fusarium graminearum spike inoculation to verify the Fhb-7EL efficacy in DW. Infection outcomes confirmed previous observations in BW, with >90% reduction of disease severity associated with Fhb-7EL presence vs. its absence. The same differential effect was detected on seed set and weight of inoculated spikes, with genotypes lacking Fhb-7EL having 80% reduction compared with unaffected values of Fhb-7EL carriers. In parallel, DON content in flour extracts of resistant recombinants averaged 0.67 ppm, a value >800 times lower than that of susceptible controls. Furthermore, as observed in BW, the same Fhb-7EL also provided the novel DW recombinants with resistance to Fusarium crown rot (~60% symptom reduction) from seedling infection with F. culmorum. Through alien segment stacking we succeeded in equipping DW with a very effective barrier against different Fusarium diseases and other positive attributes for crop security and safety.